Just War, Democracy, Democratic Peace - Mark Evans (European Journal of Political Theory, 2012)
Recent polemical controversy over whether a just war can be fought in order to promote democracy has discouraged serious consideration of the relationship between principles in just war theory and the democratic ideal. This article seeks to uncover some dimensions of that relationship, contending that while no plausible version of the theory would justify a war for democratic imposition, there are nevertheless important affinities and connections with democracy.